2021
DOI: 10.3390/microorganisms9091837
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Dynamics of Signaling Cascades and Virulence Factors of B. cinerea during Tomato Cell Wall Degradation

Abstract: The ascomycete Botrytis cinerea is one of the most relevant plant pathogenic fungi, affecting fruits, flowers, and greenhouse-grown crops. The infection strategy used by the fungus comprises a magnificent set of tools to penetrate and overcome plant defenses. In this context, the plant-pathogen communication through membrane receptors and signal transduction cascades is essential to trigger specific routes and the final success of the infection. In previous reports, proteomics approaches to B. cinerea signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
2
8
0
Order By: Relevance
“…IPP is the first precursor in the biosynthesis of terpenes in fungi, including toxins [ 69 ]. This result is consistent with our previous knowledge of glucose as an inductor of toxins production in B. cinerea [ 12 ]. Furthermore, this could indicate that EVs transport the precursors of Botrytis toxins to the plant to reinforce their production in the zone of infection.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…IPP is the first precursor in the biosynthesis of terpenes in fungi, including toxins [ 69 ]. This result is consistent with our previous knowledge of glucose as an inductor of toxins production in B. cinerea [ 12 ]. Furthermore, this could indicate that EVs transport the precursors of Botrytis toxins to the plant to reinforce their production in the zone of infection.…”
Section: Resultssupporting
confidence: 94%
“…All these results are consistent with previous analysis of the group, where it was reported that Under GLU condition, the mevalonate pathway is upregulated due to the production of toxins (botryoidal and dihydrobotrydial) [ 12 ]; and under TCW condition, the secretion of cell wall degrading enzymes was upregulated [ 12 ]. The difference in BP enrichment of EVs in both assayed conditions reveals a connection between the cargo and the environmental signals, which is essential to host adaptation during the infection process.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The evolutionary path taken by these polyxenous pathogens to diversify their host range is particularly intriguing, but molecular mechanisms driving these evolutionary changes are largely unknown. Several studies suggest that the virulence across plant species is enabled by complex interactions that include key fungal processes such as oxidative stress response (N’Guyen et al, 2021) and cell wall integrity (Cui et al, 2021; Escobar-Niño et al, 2021).…”
Section: Introductionmentioning
confidence: 99%